THE RUBLE POLICY IN THE TURKESTAN GENERAL-GOVERNORSHIP - Feruza Amonova (Web of Journals Publishing, 2025)
This article examines the consequences of the economic colonial policy of the Russian Empire in the Turkestan General-Governorship during the second half of the 19th century and the early 20th century, focusing on the involvement of financial institutions in monetary relations, changes in the monetary system, the transition to the ruble system, and the results of reforms, based on national sources and documents from the National Archive of Uzbekistan.
Keywords: economy, colonialism, reform, coin, ruble, kopeck, banknote.